Circulating antigen tests and urine reagent strips for diagnosis of active schistosomiasis in endemic areas - Ochodo, Eleanor A (Cochrane Database Syst Rev, 2015)
BACKGROUND: Point‐of‐care (POC) tests for diagnosing schistosomiasis include tests based on circulating antigen detection and urine reagent strip tests. If they had sufficient diagnostic accuracy they could replace conventional microscopy as they provide a quicker answer and are easier to use. OBJECTIVES: To summarise the diagnostic accuracy of: a) urine reagent strip tests in detecting active Schistosoma haematobium infection, with microscopy as the reference standard; and b) circulating antigen tests for detecting active Schistosoma infection in geographical regions endemic for Schistosoma mansoni or S. haematobium or both, with microscopy as the reference standard. SEARCH METHODS: We searched the electronic databases MEDLINE, EMBASE, BIOSIS, MEDION, and Health Technology Assessment (HTA) without language restriction up to 30 June 2014. SELECTION CRITERIA: We included studies that used microscopy as the reference standard: for S. haematobium, microscopy of urine prepared by filtration, centrifugation, or sedimentation methods; and for S. mansoni, microscopy of stool by Kato‐Katz thick smear. We included studies on participants residing in endemic areas only. DATA COLLECTION AND ANALYSIS: Two review authors independently extracted data, assessed quality of the data using QUADAS‐2, and performed meta‐analysis where appropriate. Using the variability of test thresholds, we used the hierarchical summary receiver operating characteristic (HSROC) model for all eligible tests (except the circulating cathodic antigen (CCA) POC for S. mansoni, where the bivariate random‐effects model was more appropriate). We investigated heterogeneity, and carried out indirect comparisons where data were sufficient. Results for sensitivity and specificity are presented as percentages with 95% confidence intervals (CI). MAIN RESULTS: We included 90 studies; 88 from field settings in Africa. The median S. haematobium infection prevalence was 41% (range 1% to 89%) and 36% for S. mansoni (range 8% to 95%). Study design and conduct were poorly reported against current standards. Tests for S. haematobium Urine reagent test strips versus microscopy Compared to microscopy, the detection of microhaematuria on test strips had the highest sensitivity and specificity (sensitivity 75%, 95% CI 71% to 79%; specificity 87%, 95% CI 84% to 90%; 74 studies, 102,447 participants). For proteinuria, sensitivity was 61% and specificity was 82% (82,113 participants); and for leukocyturia, sensitivity was 58% and specificity 61% (1532 participants). However, the difference in overall test accuracy between the urine reagent strips for microhaematuria and proteinuria was not found to be different when we compared separate populations (P = 0.25), or when direct comparisons within the same individuals were performed (paired studies; P = 0.21). When tests were evaluated against the higher quality reference standard (when multiple samples were analysed), sensitivity was marginally lower for microhaematuria (71% vs 75%) and for proteinuria (49% vs 61%). The specificity of these tests was comparable. Antigen assay Compared to microscopy, the CCA test showed considerable heterogeneity; meta‐analytic sensitivity estimate was 39%, 95% CI 6% to 73%; specificity 78%, 95% CI 55% to 100% (four studies, 901 participants). Tests for S. mansoni Compared to microscopy, the CCA test meta‐analytic estimates for detecting S. mansoni at a single threshold of trace positive were: sensitivity 89% (95% CI 86% to 92%); and specificity 55% (95% CI 46% to 65%; 15 studies, 6091 participants) Against a higher quality reference standard, the sensitivity results were comparable (89% vs 88%) but specificity was higher (66% vs 55%). For the CAA test, sensitivity ranged from 47% to 94%, and specificity from 8% to 100% (four studies, 1583 participants). AUTHORS' CONCLUSIONS: Among the evaluated tests for S. haematobium infection, microhaematuria correctly detected the largest proportions of infections and non‐infections identified by microscopy. The CCA POC test for S. mansoni detects a very large proportion of infections identified by microscopy, but it misclassifies a large proportion of microscopy negatives as positives in endemic areas with a moderate to high prevalence of infection, possibly because the test is potentially more sensitive than microscopy. 23 April 2019 No update planned Other Reliable evidence with clear conclusions. All eligible published studies found in the last search (30 Jun, 2014) were included.